Prolonging storability of Indian gooseberry (Emblica officinalis) under semi-arid ecosystem of Gujarat - Singh, Sanjay; Singh, A K; Joshi, H K (The Indian Journal of Agricultural Sciences, 2005)
An experiment was conducted during 2001-2002 to see the effect of different post-harvest treatments on storability of Indian gooseberry (Emblica officinallis Gaertn) during storage at ambient temperature. Increase in physiological loss in weight, spoilage percentage, total soluble solids, total sugar and reducing sugar and decrease in acidity, ascorbic acid with advancement of storage period were general phenomena in all the treatments. Fruits treated with calcium nitrate 1.5% + perforated polyethylene bag and GA, 100 ppm + perforated polyethylene bag recorded the least physiological loss in weight (2.12-16.00 and 2.15-16.34%) and spoilage loss (2.40-15.00% and 2.50-15.60 %) and exhibited 11 days of storage life. The same treatments also showed lowest respiratory activity (72.10-82.00 mg CO2/kg/hr and 72.00-82.10 mg C02/ kg/hr), on the last day of storage (day 13).